PENGARUH REKRUTMEN DAN PENEMPATAN KERJA TERHADAP KINERJA KARYAWAN PADA EDEN HOTEL KUTA BALI - I Kadek Yogik Dharma Putra; I Wayan Mendra; Tjok Istri Sri Harwathy (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2022)
This study aims to determine the effect of recruitment and job placement on employee performance at EDEN Hotel Kuta Bali. The sample in this study was 52 respondents, the technique of determining the sample was by non-probability sampling method. The data analysis technique used is multiple linear regression, multiple correlation analysis, model feasibility test and partial statistical test. The results showed that recruitment and placement had a positive and significant effect on employee performance. Based on the discussion of the research results and the conclusions above, the suggestions that can be given are: for the company to carry out the recruitment process in accordance with the standards set, so as to get qualified and well-performing employees, in the placement of employees adjusted to the academic achievements of the prospective employees, so that they can carry out their duties properly.